Algorithm for even power sharing using feed forward space vector modulation technique in multilevel inverter - Anand V.; Sharma V.K.; Gupta G.; Vaish V. (My University, 2025)
Advances in multilevel inverter topologies has been comprehended by advent of newer control strategies. One such strategy is feed forward space vector modulation which can be applied on single phase multilevel inverters. The algorithm, being flexible in manipulation, can be easily implemented with a digital controller. This paper proposes a feed-forward space vector modulation method with equal power sharing. Simulation is carried out in MATLAB and experimental validation has been done for a particular load on a five-level topology to verify the concept. © 2015 IEEE.